Marathi Speech Emotion recognition using Deep Learning techniques. - Ketkar, Akhilesh; Mishra, Divyansh; Nirmal, Madhur; Mulla, Faizan; Narawade, Vaibhav (Universitas Andalas, 2024)
In the project, an emotion recognition system from speech is proposed using deep learning. The goal of this project is to classify a speech signal into one of the five emotions listed below: anger, boredom, fear, happiness, and sadness. Snippets below from numerous Marathi movies and TV shows were used to construct the dataset for Marathi language samples which include 20 audio samples for anger, 19 for boredom, 5 for fear, and 11 for happiness. The proposed system first processes a speech signal from the time domain to the frequency domain using Discrete Time Fourier Transform (DTFT). Then, data augmentation is performed which includes noise injection, stretching, shifting, and pitch scaling of the speech signal. Next, feature extraction is performed in which 5 features were selected, which include Mel Frequency Cepstral Coefficients (MFCC), Zero Crossing Rate (ZCR), Chroma STFT, Mel Spectrogram, and Root mean square value. These features were then fed to a Convolutional Neural Network (CNN). The efficiency of the suggested system employing the CNNs is supported by experimental findings. This model’s accuracy on the test data is 80.33%, and its f1 values for anger, boredom, fear, happiness, and sadness are 0.85, 0.83, 0.50, 0.62, and 0.84, respectively.